Navigating the Digital Frontier: Future Trends in E-Commerce, E-Marketing, And Fashion E-Retail - Sahrawat, Shrruti (Journal of Global Economy, Business and Finance, 2024)
E-marketing has revolutionized commerce, integrating modern technology with traditional principles. The internet's pivotal role in communication and commerce has reshaped the fashion industry, fueling the rise of online fashion shopping. With significant growth prospects and evolving consumer habits, understanding the dynamics of e-tailing is crucial. This comprehensive overview delves into the evolution of e-commerce, the impact of digital marketing on fashion, consumer behavior trends, and the role of sustainability in e-tailing. Furthermore, it explores future trends such as personalized shopping experiences, augmented reality integration, and sustainability initiatives, shaping the future landscape of fashion e-tailing.